Is the Sense‐Data Theory a Representationalist Theory?. (December 2014) - Macpherson, Fiona
Abstract Is the sense‐data theory, otherwise known as indirect realism, a form of representationalism? This question has been underexplored in the extant literature, and to the extent that there is discussion, contemporary authors disagree. There are many different variants of representationalism, and differences between these variants that some people have taken to be inconsequential turn out to be key factors in whether the sense‐data theory is a form of representationalism. Chief among these are whether a representationalist takes the phenomenal character of an experience to be explicable in virtue of the properties of an experience that represent something or explicable in virtue of that which gets represented. Another is whether representationalists hold a non‐reductionist, or naturalistically or non‐naturalistically reductionist variant of representationalism. In addition, subtle differences in what one takes phenomenal character to be on the sense‐data theory – either awareness of sense‐data or the sense‐data themselves – together with one's account of representation, are crucial factors in determining whether sense‐data theory is compatible with representationalism. This paper explores these relationships and makes manifest the complexities of the metaphysics of two central theories of perception. 1